2001
DOI: 10.1037/0021-9010.86.4.709
|View full text |Cite
|
Sign up to set email alerts
|

Interviewee coaching, preparation strategies, and response strategies in relation to performance in situational employment interviews: An extension of Maurer, Solamon, and Troxtel (1998).

Abstract: Voluntary attendance at an interview coaching session was positively related to situational interview performance, controlling for job knowledge, motivation to do well, race, and sex of 213 candidates applying for promotion into several police and fire department jobs in a large city. Discrete preparation strategies (e.g., participation in study groups, participation in role-playing) were related to participation in coaching and also were related to interview performance beyond what could be accounted for by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 12 publications
3
54
0
Order By: Relevance
“…Furthermore, the research is almost exclusively on interviews. Although Campion and Campion (1987) and Griffin, Harding, Wilson, and Yeomans (2008) found no effect of coaching on interview performance, three other studies Maurer et al, 2001;Tross & Maurer, 2008) indicate that coaching and other preparation strategies do improve performance. Particularly relevant is Tross and Maurer's (2008) comparison of three types of coaching, which found not only that the more comprehensive the preparation the better the interview performance but also, of importance, that coaching increased knowledge about interviews and this knowledge fully mediated the relationship of coaching with interview outcomes.…”
Section: Experience and Learningmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the research is almost exclusively on interviews. Although Campion and Campion (1987) and Griffin, Harding, Wilson, and Yeomans (2008) found no effect of coaching on interview performance, three other studies Maurer et al, 2001;Tross & Maurer, 2008) indicate that coaching and other preparation strategies do improve performance. Particularly relevant is Tross and Maurer's (2008) comparison of three types of coaching, which found not only that the more comprehensive the preparation the better the interview performance but also, of importance, that coaching increased knowledge about interviews and this knowledge fully mediated the relationship of coaching with interview outcomes.…”
Section: Experience and Learningmentioning
confidence: 91%
“…Relative to the significant number of self-help books and commercial coaching businesses available, there has been less empirical research on the effect of preparation on selection test performance Maurer, Solamon, Andrews, & Troxtel, 2001). Furthermore, the research is almost exclusively on interviews.…”
Section: Experience and Learningmentioning
confidence: 99%
“…Job candidates for higherlevel positions may have better verbal and social skills and higher cognitive ability, thus are more capable of successfully faking, especially in more susceptible situational interviews. Finally, it has been found that attendance in an interview coaching session improved performance in situational interviews (Maurer, Solamon, Andrews, & Troxtel, 2001). …”
Section: Structured Interviewsmentioning
confidence: 99%
“…In fact, in our observations within this setting (Maurer et al, 2001), during the interview process coaching seems to encourage candidates to organize answers in a chronological, logical, and easy-to-follow manner, and to even do things like use paper and pencil to write notes before giving an answer. In short, coaching seems to help people be well organized and thoughtful which can enhance performance in a structured interview.…”
Section: Discussionmentioning
confidence: 94%
“…This being the case, interviewees might sometimes prepare for important interviews, and can be coached in an effort to increase their interview performance. A small amount of research has examined the effects of preparation and coaching on performance by interviewees and has shown that performance might be enhanced (Campion & Campion, 1987;Maurer, Solamon, Andrews, & Troxtel, 2001;Tross & Maurer, 1999). Further, there is some indication that coaching might affect applicant relations, reactions to the testing process and possibly even contribute to a reduction in test-related litigation (Solamon, 1999).…”
Section: Introductionmentioning
confidence: 97%